Bioaccessibility of carotenoids from plant and animal foods. (30th January 2019) - Chacón‐Ordóñez, Tania; Carle, Reinhold; Schweiggert, Ralf
Abstract: The frequent consumption of carotenoid‐rich foods has been associated with numerous health benefits, such as the supply of provitamin A. To exert these health benefits, carotenoids need to be efficiently liberated from the food matrix, micellized in the small intestine, taken up by the enterocytes and absorbed into the human blood stream. Enormous efforts have been made to better understand these processes. Because human studies are costly, labor‐intense and time‐consuming, the evaluation of carotenoid liberation and micellization at the laboratory scale using simulated in vitro digestion models has proven to be an important tool for obtaining preliminary results prior to conducting human studies. In particular, the liberation from the food matrix and the intestinal micellization can be mimicked by simulated digestion, yielding an estimate of the so‐called bioaccessibility of a carotenoid. In the present review, we provide an overview of the carotenoid digestion process in vivo, the currently used in vitro digestion models and the outcomes of previous bioaccessibility studies, with a special focus on correlations with concomitantly conducted human studies. Furthermore, we advocate for the on‐going requirement of better standardized digestion protocols and, in addition, we provide suggestions for the complementation of the acquired knowledge and current nutritional recommendations. © 2018 Society of Chemical Industry